One-step synthesis of magnetic composites of cellulose@iron oxide nanoparticles for arsenic removal - Yu, Xiaolin; Tong, Shengrui; Ge, Maofa; Zuo, Junchao; Cao, Changyan; Song, Weiguo (Journal of materials chemistry. A, Materials for energy and sustainability, 2013)
Composite materials, containing magnetic nanoparticles and cellulose, were synthesized by one-step co-precipitation using NaOH–thiourea–urea aqueous solution for cellulose dissolution. The NaOH in cellulose solution acted as the precipitant of iron oxide nanoparticles, and low-cost cellulose was used as the template to promote the growing of nanoparticles in the cellulose matrix. The method provided a facile, “green” pathway for the fabrication of magnetic nanomaterials. The synthesized cellulose@iron oxide nanoparticles were characterized by FTIR, XRD, SEM, TEM, XPS, TG and VSM. The FTIR, XRD and XPS results demonstrated the formation of Fe₂O₃ nanoparticles in the composite materials after the co-precipitation. SEM and TEM characterization showed that the Fe₂O₃ nanoparticles were dispersed in the cellulose matrix due to the synergistic effect. Magnetometric measurements revealed that the resultant composites of cellulose@Fe₂O₃ nanoparticles exhibited a sensitive magnetic-induced behavior and could be easily separated from aqueous solution through the external magnetic field. The composite materials were applied to remove arsenic from aqueous solution. The results showed that the magnetic nanoparticle composites displayed excellent adsorption efficiency of arsenic compared with other magnetic materials reported, and the Langmuir adsorption capacities of the composites for the removal of arsenite and arsenate were 23.16 and 32.11 mg g⁻¹, respectively.